Gambaran Penerapan Cuci Tangan Pakai Sabun (CTPS) di SD Negeri 283 Dusun Waitomu Kecamatan Leihitu Kabupaten Maluku Tengah - Rusdin Wally; Sintia Nurdin (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Handwashing with Soap (CTPS) is the activity of cleaning hands using clean, running water and soap to remove dirt, oil, and various germs such as viruses, bacteria, and parasites that may cling to the skin. As one of the most effective, simplest, and most affordable methods of preventing infectious diseases, CTPS is highly important to practice consistently, especially among students at Public Elementary School 283 located in Waitomu Hamlet, Leihitu District, Central Maluku Regency. However, observations indicate that after school activities or playtime, several students still show reluctance to wash their hands, which may be influenced by low awareness, limited understanding of hygiene, insufficient supervision, or the absence of strong daily habits related to cleanliness. This issue reflects the need for more structured hygiene education, continuous reminders, and interactive learning methods to instill good handwashing habits. In addition, improving supporting facilities—such as accessible handwashing stations, adequate soap supply, and visual posters—can motivate students to practice CTPS more regularly. Strengthening CTPS awareness and habits is expected to reduce the risk of disease transmission, foster a healthier school environment, and encourage students to adopt lifelong hygiene practices that benefit both their personal well-being and the wider community.